Inside Back Cover: Coherent Vibration and Femtosecond Dynamics of the Platinum Complex Oligomers upon Intermolecular Bond Formation in the Excited State (Angew. Chem. Int. Ed. 51/2020). Issue 51 (19th October 2020) - Iwamura, Munetaka; Fukui, Airi; Nozaki, Koichi; Kuramochi, Hikaru; Takeuchi, Satoshi; Tahara, Tahei
Abstract : Intermolecular bond formations among Pt atoms in oligomers of Pt II complexes are induced by photo‐irradiation. Femtosecond time‐resolved absorption measurements for aqueous solutions of K2 [Pt(CN)4 ] recorded clear oscillations of transient absorption in the first few picoseconds with complex dynamics. The oscillations arise from the Pt−Pt stretch motions of the S1 trimer and S1 tetramer. Analysis of the oscillations provides clear assignments of the oligomers, as described by M. Iwamura, T. Tahara, and co‐workers in their Research Article on page 23154 .